Norms in social representations: Two studies with French young drivers. - Sandrine Gaymard (European Journal of Psychology Applied to Legal Context, 2009)
This paper deals with a representational and conditional approach regarding norms. In the framework of social representations, conditionality is linked to individual practices or behaviors. Taking a questionnaire based on conditional scenarios that permitted to articulate individual and group behaviors to the prescriptions of Highway Code, two studies manipulating instructions with samples of young drivers were designed. The first study confirmed that conditional transgressions declared through individual practices refer to what young drivers fell acceptable to contravene. In the second study, substitution instructions i.e., to answer at the scenario “to be well-seen by yours friends” or “to be badly-seen by yours friends”, and standard instructions (e.g., “response as you behave”), were administrated, using a scenario of speed limit, to study the influence of norms in subjects’ responses. A multiple regression analysis showed that the responses were mediated by normative models. In conclusion, the studies illustrated an important complementary aspect of road safety concerning the social perception of rules, the influence of normative models and theirs impacts on young driver behavior.